Effect of soil type and grade of concrete on amount of steel for reinforced concrete hospital building with seismic design - Syaqierah Tang, Saka (2018)
Current practice in Malaysia nowadays is not consider the seismic precaution since Malaysia is not located in active seismic fault zone. Most building in Malaysia had been designed based on BS8110. Engineers considered Malaysia is safe from earthquake until in June 2015, Malaysia was surprised by an unexpected tremor with magnitude Mw 6.0 on 7.15 am in the morning in Ranau, Sabah. The tremors was felt in Kundasang, Tambunan, Pedalaman, Tuaran, Kota Kinabalu, and Kota Belud. This incident open people’s eyes and minds about the risk of earthquake. Since hospital building is one of significant structure for public necessity as an medical institution and need to accommodate lot of people, it must be able to resist seismic load whenever earthquake happen and it is strongly related with the strength of the structure. Hence, this research investigated the amount of steel reinforcement for reinforced concrete hospital building with seismic design. The analysis conducted by using four types of soil and two grades of concrete. There are nine models used for the analysis designed based on Eurocode 8 and conducted by using Tekla Structural Design software. Based on the result, it can be concluded that Soil Type D required steel reinforcement 110% higher when compared to non seismic design when used concrete grade G30. While for the effect of grade of concrete, grade of concrete G30 required more amount of steel reinforcement than grade of concrete G40 around 41.8% when the structure built on Soil Type D. Therefore, type of soil and grade of concrete should be taken into consideration for seismic building design.